Discontinuation of disease-modifying therapy in patients with multiple sclerosis over age 60. (April 2019) - Hua, Le H; Fan, Tracey H; Conway, Devon; Thompson, Nicolas; Kinzy, Tyler G
Background: The risk–benefit ratio of continuing immunomodulating disease-modifying therapy (DMT) in older multiple sclerosis (MS) patients is unknown. Objective: To evaluate clinical and patient-reported outcomes after stopping DMT in older MS patients. Methods: Retrospective, observational study identifying patients from our MS clinics who were aged over 60 and on DMT > 2 years. Cause-specific Cox proportional hazards regression modeled time to discontinuation and time to reinitiation of therapy. Pre- and post-discontinuation comparisons of Performance Scales (PS), Timed 25-Foot Walk, and Patient Health Questionnaire-9 (PHQ9) were analyzed using linear mixed models. Results: A total of 600 patients were included, with 178 (29.7%) discontinuing. Discontinuers were 2.2 years older, had 3.2 years longer disease duration, and 1.6 years lesser treatment exposure. Providers initiated discontinuation more than patients (68.0%). Only one clinical relapse occurred in discontinuers. A proportion (10.7%) reinitiated DMT. Provider-initiated discontinuers restarted less often (hazard ratio (HR): 0.34; 95% confidence interval (CI): 0.12–0.9). In discontinuers, relapsing-remitting patients had lower PS on average than primary progressive. Provider-initiated discontinuation was associated with lower PS than patient- initiated discontinuation. PHQ9 scores appeared higher in those stopping intravenous (IV) therapies than interferons. Lower PS and PHQ9 indicate better outcomes. Conclusion: Most patients over age 60, who discontinued DMT, remained off DMT. This study provides real-world data that may guide clinicians considering discontinuing DMT.